PENGGUNAAN METODE YURIDIS NORMATIF DALAM MEMBUKTIKAN KEBENARAN PADA PENELITIAN HUKUM - Muhammad Zainuddin; Aisyah Dinda Karina (Universitas Karya Husada Semarang, 2023)
Legal issues must be studied scientifically through various legal studies so as to be able to present the right solution. Legal research itself must use methods that are in accordance with existing legal problems. This research method is urgent because it will determine the truth or validity of the results of a study. Inappropriate methods affect the results of the study itself. Broadly speaking, legal research methods are divided into two, namely empirical and normative. Normative legal research is influenced by pure legal doctrine. The discussion in this research is more about why normative juridical methods are needed in proving the truth in legal research?, and what is the mechanism for using normative juridical methods in proving the truth in legal research?. This study aims to analyze the urgency of using normative juridical methods in proving the truth in legal research, and to find out the mechanisms and stages that must be carried out in using normative juridical methods in proving the truth in legal research. The statutory approach is very important to use in analyzing a legal problem, the settlement of issues or legal problems must of course be based on constructive arguments and on the basis of rules or positive law. The stages in normative legal research begin with secondary data collection through literature study, then analysis is carried out using deductive logical thinking. deductive by emphasizing norms, jurisprudence and doctrine. Then the final stage is the researcher by making a decision or a conclusion.